2013
DOI: 10.1371/journal.pntd.0002005
|View full text |Cite|
|
Sign up to set email alerts
|

Bispidine-Amino Acid Conjugates Act as a Novel Scaffold for the Design of Antivirals That Block Japanese Encephalitis Virus Replication

Abstract: BackgroundJapanese encephalitis virus (JEV) is a major cause of viral encephalitis in South and South-East Asia. Lack of antivirals and non-availability of affordable vaccines in these endemic areas are a major setback in combating JEV and other closely related viruses such as West Nile virus and dengue virus. Protein secondary structure mimetics are excellent candidates for inhibiting the protein-protein interactions and therefore serve as an attractive tool in drug development. We synthesized derivatives con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…All cell lines and their growth conditions have been described before1027. Porcine kidney (PS) cells, Vero and BHK-21 cells were grown in the minimal essential medium (MEM) containing 10% FBS, Earl's salts and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…All cell lines and their growth conditions have been described before1027. Porcine kidney (PS) cells, Vero and BHK-21 cells were grown in the minimal essential medium (MEM) containing 10% FBS, Earl's salts and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently identified amino acid conjugates of 3,7-diazabicyclo[3.3.1]nonane, commonly called bispidine (Bisp-W), as novel inhibitor of JEV replication [18]. To identify if JEV replication is required for TER disruption, caco-2 cells were infected with JEV and Bisp-W was added at 1 h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVEC) were purchased from BD Biosciences and grown in endothelial cell culture medium supplied with the cell line. JEV-Vellore strain was used throughout the study and viral titers were estimated as described previously [18]. For generation of virus-free culture supernatants, Caco2 cells were infected with JEV at an MOI of 5 pfu/cell and at around 44 hour post-infection (h pi) supernatants were collected and clarified through Amicon columns with 100 k Da cut-off (Merck-Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Supportive care directed to control convulsions and maintenance of airway, fluid and electrolyte balance plays a key role in treatment efficacy during the acute phase. Although, treatment with diethyldithiocarbamate (Saxena et al, 2003), Lipid-complexed small interfering RNA (siRNA) (Kumar et al, 2006), Rosmarinic acid (Swarup et al, 2007), Pentoxifylline (Sebastian et al, 2009), Arctigenin (a lignin derived from the Greater Burdock (Arctiumlappa) (Hayashi, 2010), Peptideconjugated phosphorodiamidatemorpholino oligomers (Anantpadma et al, 2010), Minocycline (semi-synthetic derivative of tetracycline) (Dutta & Basu, 2011), Tilapia hepcidin 1-5 (Antimicrobial peptide) (Huang et al, 2011), Griffithsin (Ishag et al, 2013), Bispidine (amino acid conjugate of 3,7-diazabicyclononane) (Haridas et al, 2013), Mycophenolic acid (Sebastian et al, 2011), Luteolin (Fan et al, 2016 and anti-miR301a therapy (Hazra et al, 2017) have been found as promising candidates against JE infection that were attempted and showed protective effect in laboratory models. Their efficacy in the hospital settings is a big challenge which needs further assessment and increased availability to the needful.…”
Section: Treatmentmentioning
confidence: 99%